The role of PPARβ/δ in melanoma metastasis - Lim, Jonathan Chee Woei (2018)
Background: Peroxisome proliferator–activated receptor (PPAR) β/δ, a ligand-activated transcription factor, is involved in diverse biological processes including cell proliferation, cell differentiation, inflammation and energy homeostasis. Besides its well-established roles in metabolic disorders, PPARβ/δ has been linked to carcinogenesis and was reported to inhibit melanoma cell proliferation, anchorage-dependent clonogenicity and ectopic xenograft tumorigenicity. However, PPARβ/δ’s role in tumour progression and metastasis remains controversial. Methods: In the present studies, the consequence of PPARβ/δ inhibition either by global genetic deletion or by a specific PPARβ/δ antagonist, 10h, on malignant transformation of melanoma cells and melanoma metastasis was examined using both in vitro and in vivo models. Results: Our study showed that 10h promotes epithelial-mesenchymal transition (EMT), migration, adhesion, invasion and trans-endothelial migration of mouse melanoma B16/F10 cells. We further demonstrated an increased tumour cell extravasation in the lungs of wild-type mice subjected to 10h treatment and in Pparβ/δ−/− mice in an experimental mouse model of blood-borne pulmonary metastasis by tail vein injection. This observation was further supported by an increased tumour burden in the lungs of Pparβ/δ−/− mice as demonstrated in the same animal model. Conclusion: These results indicated a protective role of PPARβ/δ in melanoma progression and metastasis.